2019
DOI: 10.31788/rjc.2019.1224034
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Mineralogical Phase of Ancient Brick Samples of Kathmandu Valley (Nepal) Using XRD and Ftir Analysis

Abstract: The total eight clay brick samples including five archaeologically importance samples from different historical sites and three samples from more than a century old buildings of Kathmandu valley were collected and their mineralogical phases were characterized using X-ray diffraction and Fourier transform infrared spectroscopic methods in this study. Mineralogical phases existed in these archaeological and ancient clay bricks are identified as quartz, feldspars, spinel, muscovite, margarite and hematite in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…1 (Ghale 2018). It is meaningful to mention here that the mineralogical phase of these seven ancient clay brick samples was reported to be consisted mainly of quartz, feldspars, spinel, margarite, hematite and muscovite type of mica minerals from previous works (Ghale et al 2018). In this study, the physical properties of water absorption capacity, apparent porosity and bulk density of the analyzed clay brick samples were estimated using following equations (1), (2) and (3) (ASTM C20-00 2015), respectively, were D is the weight of brick sample in dry condition (g), S is the weight of brick sample in saturated condition (g) and V is volume of outer sides (cm 3 ) of the brick sample specimens.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…1 (Ghale 2018). It is meaningful to mention here that the mineralogical phase of these seven ancient clay brick samples was reported to be consisted mainly of quartz, feldspars, spinel, margarite, hematite and muscovite type of mica minerals from previous works (Ghale et al 2018). In this study, the physical properties of water absorption capacity, apparent porosity and bulk density of the analyzed clay brick samples were estimated using following equations (1), (2) and (3) (ASTM C20-00 2015), respectively, were D is the weight of brick sample in dry condition (g), S is the weight of brick sample in saturated condition (g) and V is volume of outer sides (cm 3 ) of the brick sample specimens.…”
Section: Methodsmentioning
confidence: 74%
“…The durability assessment of different types of clay bricks is mainly based on their technical physico-sintering and mechanical properties. However, such technical properties of the archaeological clay brick samples of Kathmandu valley are not reported in scientific communities, although mineralogy of the archaeological bricks (Ghale et al 2018), fired clay bricks at different temperatures (Bohara et al 2018) and ceramic tiles (Buthathoki et al 2018a, 2018b) were recently reported by some of the present researchers in Nepal. It was reported that the mineralogical phases existed in the archaeological clay brick samples collected from Kathmandu valley were identified as quartz, feldspars, spinel, muscovite type of mica mineral and hematite, and such clay bricks were considered to be fired at 900-1000 °C for their production (Ghale et al 2018).…”
Section: Introduction and Objectivementioning
confidence: 69%
See 1 more Smart Citation
“…The clay with high sand makes brick less cohesive, weak and broken corner. It was reported that type of clay brick samples collected from Kathmandu valley were identified as quartz, feldspars, mica mineral and hematite, and such clay bricks are considered to be fired at 900-1000°C [22]. Improper mixing proportion of clay particles creates shrinkage or expansion.…”
Section: Effect Of Clay Composition On Characteristics Of Bricks I) Cmentioning
confidence: 99%
“…The quality assessment of different types of clay bricks is based on their mineralogical, physicosintering and mechanical properties. However, such technical properties of the clay bricks [19,20] and ceramic tiles [21,22] of Nepal were studied by very few research groups in Nepal. Considering these facts, the present research work is focused to carry out an investigation of the firing temperature effect on the mineralogical phases of the fired clay brick samples by XRD and FTIR analysis.…”
Section: Introductionmentioning
confidence: 99%